(p, h)-Convex Functions Associated with Hadamard and Fejér-Hadamard Inequalities via k-Fractional Integral Operators. (28th April 2022) - Zhang, Xiujun; Farid, Ghulam; Demirel, Ayşe Kübra; Jung, Chahn Yong
Abstract : In this article, generalized versions of the k -fractional Hadamard and Fejér-Hadamard inequalities are constructed. To obtain the generalized versions of these inequalities, k -fractional integral operators including the well-known Mittag-Leffler function are utilized. The class of (p, h )-convex functions for Hadamard-type inequalities give the generalizations of results which have been proved in literature for p -convex, h -convex, and several functions deducible from these two classes.